Draft regional agricultural sector programme : indicative programme of activities 1987-1991 (CARICOM Secretariat GeorgetownGY, 1987)
Reviews agricultural sector and analyses current economic and social policies. Discusses the mission, goals, and objectives of the agricultural sector. Outlines strategy of the agricultural sector in various sub-sectors including livestock, fisheries, forestry, and agro-industry. Summarises programme areas for the sector which should receive priority treatment over the five year period 1987-1991 in order for the sector to improve its contribution to the regional development process. Outlines implementation strategy.
IDS